KEDUDUKAN HAKIM AD-HOC PADA PENGADILAN TIPIKOR (TINDAK PIDANA KORUPSI) DITINJAU DARI UNDANG-UNDANG NOMOR 48 TAHUN 2009 TENTANG KEKUASAAN KEHAKIMAN - TITIN APRIANI (GANEC SWARA, 2019)
This research is a library research that uses data in the form of books, laws, articles, journals and other literature related to the title, while the technique and data collection is by collecting various ideas, theories and concepts of various literature that are centered on the process of comparison between the evidence or other laws. The results of the study concluded that the ruling of the Constitutional Court against the position of the ad hoc judge is appropriate because it gives the same position on a different matter precisely caused injustice.   In addition to having the authority to check, prosecute, and break the criminal corruption, adhoc judges also have the authority to examine the criminal case of money laundering that the original criminal act is a corruption crime. So here corruption as the original criminal act is often referred to as predicate crimes. It is no less important that the role and authority of the adhoc judge specialising in the association of article 6 letter c The authority of the Court of Law to handle a strict follow-up in another law is determined as a corruption criminal act